2023
DOI: 10.24017/science.2022.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Diseases Classification using Hybrid Transfer-Learning DenseNet201-Based and Random Forest Classifier

Abstract: There are several disease kinds in global populations that may be related to human lifestyles, social, genetic, economic, and other factors related to the nature of the country they live in. Most of the recent studies have focused on investigating prevalent diseases that spread in the population in order to minimize mortality risks, choose the best method for treatment, and improve community healthcare. Kidney disease is one of the most widespread health problems in modern society. This study focuses on kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Both the algorithms achieved an approximately 85% precision and F1-score, whereas our model achieved more than 99%. With the same 3 different kidney planes for 4 classes, 99.44% was achieved by the authors of [30]. They used a DenseNet algorithm, and their model had 19.82 million more parameters than our model.…”
Section: Comparison With the State-of-the-art Methodsmentioning
confidence: 87%
See 3 more Smart Citations
“…Both the algorithms achieved an approximately 85% precision and F1-score, whereas our model achieved more than 99%. With the same 3 different kidney planes for 4 classes, 99.44% was achieved by the authors of [30]. They used a DenseNet algorithm, and their model had 19.82 million more parameters than our model.…”
Section: Comparison With the State-of-the-art Methodsmentioning
confidence: 87%
“…The results indicated that their YOLOv7 architecture design outperformed the YOLOv7 tiny architecture design, achieving a mAP50 of 0.85, a precision of 0.882, a sensitivity of 0.829, and an F1-score of 0.854. A study by Abdalbasit et al [30] focused on identifying the three types of kidney abnormalities (stones, cysts, and tumors) using AI techniques on a dataset of over 12,000 CT images. A hybrid approach of pre-trained models and machine-learning algorithms was used, and the Densenet-201 model and random-forest classification yielded an accuracy rate of 99.44%.…”
Section: Deep-learning Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Through testing on a dataset of 150 photos, the suggested classifier is compared to the other rival machine learning classifiers and provides a higher accuracy of 96.67%. [36] this study uses a dataset of 12,446 computational thinking (CT) urogram and whole abdomen images to focus on kidney stones, cysts, and tumors-the three most common types of renal illness. The goal is to advance the field of artificial intelligence research while developing a kidney disease diagnosis system that is artificial intelligent AI-based.…”
Section: Salekin and Stankovicmentioning
confidence: 99%